Round robin testing of a percolation column leaching procedure. (September 2016) - Geurts, Roeland; Spooren, Jeroen; Quaghebeur, Mieke; Broos, Kris; Kenis, Cindy; Debaene, Luc
Highlights: Statistical analysis of round robin test results of column leaching tests in Flanders (Belgium). The relation between reproducibility and repeatability is quantified. The reproducibility is discussed in the context of legal limits. The influence of materials, elements and fractions is reported. The performance of different labs is compared. Abstract: Round robin test results of a percolation column leaching procedure (CEN/TS 14405:2004), organised by the Flemish Institute for Technological Research (VITO), over a time span of 13 years with a participation of between 8 and 18 different laboratories are presented and discussed. Focus is on the leachability of heavy metals As, Cd, Cr, Cu, Hg, Ni, Pb and Zn from mineral waste materials. By performing statistical analyses on the obtained results, insight into the reproducibility and repeatability of the column leaching test is gathered. A ratio of 1:3 between intra- and inter-laboratory variability is found. The reproducibility of the eluates' element concentrations differ significantly between elements, materials and fractions (i.e. different liquid-to-solid ratios). The reproducibility is discussed in light of the application of the column leaching test for legal and environmental policy purposes. In addition, the performances of laboratories are compared.